Pelaksanaan Pembelajaran Daring pada Masa Pandemi Covid-19 di Program Studi Pendidikan PKn Universitas Tadulako - Antonius Palimbong (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2020)
The impact of the Covid-19 pandemic affects psychological conditions and changes in human behavior that are broader in the longer term. It also has an impact on the education system in Indonesia. Tadulako University implements Work From Home policy for lecturers/home study for students. This study aims to analyze the implementation of online learning during the Covid-19 pandemic in the PKn Education Study Program of Tadulako University. This research uses descriptive method with qualitative approach with informant consisting of lecturers and students in PKn Education. Based on the results of research, it can be known that the implementation of learning carried out during the Covid-19 pandemic in PKn Education uses an online model with applications in the form of: LMS, zoom, whatsapp, telegram, google classroom. The implementation of online learning went smoothly, although it was felt less than ideal. Student learning outcomes vary from unsatisfactory, sufficient to good. The obstacles faced by students and lecturers in online learning include: the availability of internet quota, unstable networks, and supporting tools such as gadgets and laptops. Online learning is considered effective if the internet network system is maintained or in the area where students live, but a more varied model is needed to remain attractive if used in the long term.